Grazing intensity and human activity intensity data sets on the Qinghai‐Tibetan Plateau during 1990–2015. (14th July 2021) - Sun, Yongxiu; Liu, Shiliang; Liu, Yixuan; Dong, Yuhong; Li, Mingqi; An, Yi; Shi, Fangning
Abstract: As the 'third pole' of the world, the Qinghai‐Tibetan Plateau (QTP) is extremely ecologically sensitive and fragile, while also facing increasing levels of human activity, especially overgrazing. In this study, livestock data from the statistical yearbook were transformed to 1 km grazing intensity raster data by integrating the net primary productivity (NPP) data for 1990, 1995, 2000, 2005, 2010 and 2015. Furthermore, the human activity intensity (HAI) data at 1 km resolution were evaluated by the entropy weight method, which applied eight types of spatial data, including grazing intensity, Night‐Time Light, population density, Gross Domestic Product (GDP) density, the ratio of cultivated land, distance to road, distance to town and the slope of the Normalized Difference Vegetation Index (NDVI). Also, the five‐year interval human activity intensity data on the QTP from 1990 to 2015 were evaluated. By preparing the historical spatial data sets of grazing intensity and human activity intensity, our study will help to explore the influence of human disturbance on the alpine ecosystems on the QTP, as well as provide effective support for the decision‐making of the government aiming to achieve regional ecosystem management and sustainable development. Abstract : The working flowchart.